Political Culture and Post-Communism
XVI, 234 p. 1 illus.
Keywords: Our understanding of the dynamics of Communist systems was substantially improved by taking political culture into account. But how much does the concept of political culture add to our empirical understanding of post-Communist Russia? The book's contributors engage with theoretical debates between political culture and competing 'rational choice' and institutionalist approaches to post-Soviet politics, and provide illustrative empirical studies of civic participation, views of national identity, the Russian criminal justice system and political violence.